Soil degradation by compaction as a function of weight distribution on the axles of agricultural tractors - Calderón, Natalia Gómez (2020)
Soil compaction caused by agricultural machinery traffic has a negative effect on a range of soil functions and ecosystem services. Using the information of the agricultural equipment registered in Costa Rica and considering that the average weight limit that resists the soil in friable conditions is 49kN per axis, three scenarios of static weight distribution were proposed in the front and rear axles. It was found that only 3.1% of the tractors with tires exceeded the weight limit, but when the tractor was analyzed with the suspended implement, it was found that the distribution of the load generates an effect in the percentage of excess weight in the axles. The more powerful tractors should use liftingimplements of less weight than their capacity, or use pulling implements so that they do not exceed the limit weight in any of their axes.